W sprawie inicjatywy ustawodawczej - Szmyt, Andrzej (Wydział Prawa i Administracji UAM, 1986)
In a form of case study the analysis concerns various aspects of legislative initiative. The author observes a possibility of widening a range of subjects of the initiative, mainly by social organizations, of institutionalizing legislative inspiration, popular inspiration. Withdrawing a bill is possible only upon obtaining a consent of the Parliament. The principle of discontinuity of works has to be refused. The analysis pertains to the specificity of the initiative of members of the Seym, unilaterality of the aspect of introducing a draft of the law is emphasised with the respect to separating from the contribution to preparation of the draft. (A form of the initiative should enable the control fulfilling exingencies, mainly passing a bill by the government. It is desirable to precise the requirements, like indicating at certain acts within preparatory works stage to condition starting the processing of the bill. It is imperative to institutionalize elements of the grounds of the draft and annexing drafts of executive acts. A notion of bill in the light of legal regulation and practice is analysed. The postulates to increase the M.P.'s influence on the bill can be realized in various organizational forms. The author admits a varied manner of carrying out the initiative subject to the stage of preparatory works, and a right to initiative within a statutory scope of activity of the entitled subject. The importance of social accessibility of the subject of initiative is emphasised, including social drafts of the law as substratum of works of the M. P.'s. In spite of the dominating governmental legislative analysis it is possible to utilize the M. P.'s activity to a higher degree. Also the activity of social subjects should become a durable factor of legislative initiatives. The analysis is concluded by the postulates on the bill of the Lawmaking Act.
On a question of legislative initiative